A systematic review of clinimetric properties of measurements of motivation for children aged 5-16 years with a physical disability or motor delay - Miller, L.; Ziviani, J.; Boyd, Roslyn (2014)
The purpose of this systematical review was to appraise the clinimetric properties of measures of motivation in children aged 5-16 years with a physical disability or motor delay. Six electronic databases were searched. Studies were included if they reported measuring motivation in school-aged children across occupational performance areas. Two reviewers independently identified measures from included articles. Evaluation of measures was completed using the COSMIN (consensus-based standards for the selection of health measurement instruments) checklist. A total of 13,529 papers were retrieved, 15 reporting measurement of motivation in this population. Two measures met criteria: Dimensions of Mastery Questionnaire (DMQ) and Pediatric Volitional Questionnaire (PVQ). There was evidence of adequate validity for DMQ, and preliminary evidence of test-retest reliability. Psychometric evidence for PVQ was poor. Both measures demonstrated good clinical utility. The large number of retrieved papers highlights the importance being attributed to motivation in clinical studies, although measurement is seldom performed. Both identified measures show promise but further psychometric research is required.